Relationship Between Marketing of Financial Services and Bank Performance in Jordan - Kurdi, Ibrahim Ali (2012)
In recent times, marketing has evolved to become the backbone of any successful business activity. This study therefore seeks to investigate the nexus between marketing cost and bank performance. The study is based on a sample of 8 out of 13 commercial banks in Jordan covering a five-year period from 2006 to 2010. The selected banks were identified based on the data availability. In this study, the role of marketing activities is related to bank performance in terms of deposits from customer, loans, profit after taxes, return on assets and return on equity. Data collected were analyzed using the Pearson Correlation Matrix and Simple Linear Regression. The results show a significant positive relationship exists between marketing cost and Jordanian bank performance based on deposits from customer, loans and profits after taxation and a negative relation exists between marketing cost and bank performance in light of return on assets. The findings further reveal that there is no significant link between marketing cost and return on equity in Jordanian banks. Growing marketing cost in improving bank performance is also evidenced and supported in the study, although the marketing role is not the single factor that determines bank performance.